Sloth on Time: Efficient Hardware-Based Scheduling for Time-Triggered RTOS - Hofer, Wanja; Danner, Daniel; Müller, Rainer; Scheler, Fabian; Schröder-Preikschat, Wolfgang; Lohmann, Daniel (Proceedings of the 33rd IEEE Real-Time Systems Symposium (RTSS 2012), 2012)
Traditional time-triggered operating systems are implemented by multiplexing a single hardware timer-the system timer-in software, having the kernel maintain dispatcher tables at run time. Our Sloth on Time approach proposes to make use of multiple timer cells as available on modern micro controller platforms to encapsulate dispatcher tables in the timer configuration, yielding low scheduling and dispatching latencies at run time. Sloth on Time instruments available timer cells in different roles to implement time-triggered task activation, deadline monitoring, and time synchronization, amongst others. By comparing the Sloth on Time kernel implementation to two commercial kernels, we show that our concept significantly reduces the overhead of time-triggered operating systems. The speed-ups in task dispatching that it achieves range up to a factor of 171x, and its dispatch latencies go as low as 14 clock cycles. Additionally, we demonstrate that Sloth on Time minimizes jitter and increases schedulability for its real-time applications, and that it avoids situations of priority inversion where traditional kernels fail by design. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.IMMD4.slotho
Keywords: Sloth; Operating Systems; Embedded Systems; Real-Time Systems; Interrupt Handling; Timers; Time-Triggered Scheduling; OSEK; AUTOSAR; Infineon TriCore